2017
DOI: 10.15446/agron.colomb.v35n1.61068
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of N, P, and K in the tubers of potato (Solanum tuberosum L. ssp. andigena) under contrasting soils of the Andean region of Colombia

Abstract: The relationship between tuber growth and demand for NPK in andigena group of potato (Solanum tuberosum L. ssp. andigena) is poorly documented under conditions of the Andean region of Colombia. It is necessary to establish a specific nutrient management for high yields to changes in edaphic-environmental supply and improve the production of Capiro and Supreme cultivars. Twelve treatments were evaluated at different stages (75-100-125-150 days after planting) of tuber growth using a repeated measures design wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
3
0
3
Order By: Relevance
“…However, the average values of total biomass obtained in this study tend to be lower, even in the high fertilization treatment (400-N). Conversely, biomass accumulation and tuber yield levels in different studies are shown to be much greater when there is a moderate application of nitrogen fertilizer (approximately 180 kg N ha -1 ), even when cultivars grow under fertilization conditions without nitrogen (Van Delden, 2001;Goméz et al 2017;Malta et al 2018). Nevertheless, the same biomass accumulation pattern is present during phenostages when nitrogen supply increases (Van Delden, 2001;Silva et al, 2013).…”
Section: Biomass and Nitrogen Partitioningmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the average values of total biomass obtained in this study tend to be lower, even in the high fertilization treatment (400-N). Conversely, biomass accumulation and tuber yield levels in different studies are shown to be much greater when there is a moderate application of nitrogen fertilizer (approximately 180 kg N ha -1 ), even when cultivars grow under fertilization conditions without nitrogen (Van Delden, 2001;Goméz et al 2017;Malta et al 2018). Nevertheless, the same biomass accumulation pattern is present during phenostages when nitrogen supply increases (Van Delden, 2001;Silva et al, 2013).…”
Section: Biomass and Nitrogen Partitioningmentioning
confidence: 99%
“…The N effect on tuber yield has been well demonstrated (Alva et al, 2002;Maltas et al, 2018). Howe-ver, the potato growth response depends largely on the nitrogen availability in the soil, which may have a considerable effect on the partitioning of assimilates and nitrogen to the different plant organs (Silva et al, 2013;Goméz et al, 2017;Ohamed et al, 2017). This balance of the distribution of biomass and nitrogen to the different compartment may have significant effects on tuber production (Machado & Sarmiento, 2012;Silva et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Las hojas absorben la luz y realizan el intercambio gaseoso, funciones que requieren una presencia activa del fósforo. Según Gómez et al (2017), la nutrición con P genera un aumento de la masa y volumen de las raíces, dándose un incremento total de la superficie de adsorción de agua y nutrientes, lo que resulta en un incremento del peso fresco de la parte aérea, resultado que se corrobora con lo observado en la figura 2A.…”
Section: Resultados Y Discusiónunclassified
“…La disponibilidad de nutrientes regula la relación de los órganos fuente/vertedero y por tanto afecta la distribución de los fotoasimilados y productividad del cultivo de papa (Li et a., 2016;Gómez et al, 2017;Grzebisz et al, 2020). Lo anterior fue corroborado en plantas con deficiencias en nitrógeno, dado que estas condiciones redujeron significativamente el área foliar, y por tanto las tasas fotosintéticas de las plantas, lo que conllevo a disminuir el suministro de los fotoasimilados por los órganos fuente hacia los órganos vertederos y de esta manera, se tuvo limitaciones en los rendimientos de los cultivos (Li et al, 2016).…”
Section: Estado Nutricionalunclassified
“…También, se ha reportado que disminuciones o excesos de nitrógeno en la fertilización del cultivo de papa, puede afectar la partición de fotoasimilados, principalmente por reducción del crecimiento del dosel ocasionando senescencia prematura de las hojas y disminución de la translocación de los fotoasimilados en etapas de llenado. Así mismo, se mencionan reducciones en las tasas fotosintéticas, en la superficie total de la hoja y en el número y peso de los tubérculos (Ruža et al, 2013;Gómez et al, 2017).…”
Section: Estado Nutricionalunclassified